Investigating the Relationship Between Chorionic Villous Sampling and Pregnancy Complications (Medical Forum Monthly, 2026)
Objective: To determine the relationship between chorionic villous sampling (CVS) and pregnancy complications by evaluating immediate procedural, antenatal, delivery, and neonatal outcomes among women undergoing first- trimester prenatal diagnosis.Study Design: Prospective observational studyPlace and Duration of Study: This study was conducted at the Department of Obstetrics and Gynaecology, Jinnah Postgraduate Medical Centre, Karachi, from September 2025 till January 2026.Methods: Pregnant women between 10 and 13+6 weeks of gestation undergoing CVS for prenatal genetic diagnosis were enrolled using non-probability consecutive sampling. Singleton pregnancies with complete follow-up until delivery were included. Baseline demographic and obstetric variables were recorded. CVS was performed via transcervical or transabdominal approaches under ultrasound guidance.Results: A total of 73 women were included with a mean age of 32.18 ± 7.32 years and mean gestational age of 11.03 ± 0.87 weeks. Transcervical CVS was performed in 43 (58.9%) cases. Immediate complications were absent in 49 (67.1%) participants, with minor symptoms such as uterine contractions in 10 (13.7%) and spotting in 14 (19.2%). Ongoing pregnancy was observed in 50 (68.5%) cases, while 37 (50.7%) remained free of antenatal complications. Vaginal delivery occurred in 39 (53.4%) women. Neonatal survival was noted in 68 (93.2%) cases, with 56 (76.7%) neonates appearing clinically normal.Conclusion: CVS is a relatively safe and effective first-trimester diagnostic procedure with low rates of maternal and fetal complications. When performed by experienced operators with appropriate follow-up, it provides substantial diagnostic benefit with acceptable risk.